Bre1-dependent H2B ubiquitination promotes homologous recombination by stimulating histone eviction at DNA breaks. Issue 21 (10th October 2018) - Zheng, Sihao; Li, Dan; Lu, Zhen; Liu, Guangxue; Wang, Meng; Xing, Poyuan; Wang, Min; Dong, Yang; Wang, Xuejie; Li, Jingyao; Zhang, Simin; Peng, Haoyang; et al.
Abstract: Repair of DNA double-strand breaks (DSBs) requires eviction of the histones around DNA breaks to allow the loading of numerous repair and checkpoint proteins. However, the mechanism and regulation of this process remain poorly understood. Here, we show that histone H2B ubiquitination (uH2B) promotes histone eviction at DSBs independent of resection or ATP-dependent chromatin remodelers. Cells lacking uH2B or its E3 ubiquitin ligase Bre1 exhibit hyper-resection due to the loss of H3K79 methylation that recruits Rad9, a known negative regulator of resection. Unexpectedly, despite excessive single-strand DNA being produced, bre1Δ cells show defective RPA and Rad51 recruitment and impaired repair by homologous recombination and response to DNA damage. The HR defect in bre1Δ cells correlates with impaired histone loss at DSBs and can be largely rescued by depletion of CAF-1, a histone chaperone depositing histones H3-H4. Overexpression of Rad51 stimulates histone eviction and partially suppresses the recombination defects of bre1Δ mutant. Thus, we propose that Bre1 mediated-uH2B promotes DSB repair through facilitating histone eviction and subsequent loading of repair proteins.